G16 Introduction to the well north project and the potential impact on child health. (27th April 2015) - Marshall, M; Hurst, H
Abstract : Background: The Health of children in the UKis generally worse in the North of England where there are higher levels of child poverty. Evidence demonstrates that early disadvantages track forward, to influence health and development in later life and that children who start behind stay behind. Whitehouse (2014) and Marmot (2010) highlight the complexities and demonstrate a clear correlation between poverty, deprivation and poor health outcomes. Aims: The intention of this paper is to introduce a Public Heath England funded project for the North of England called 'Well North'. The overarching strategic aims of which are to: Improving the health of the poorest fastestReducing levels of worklessness a cause and effect of poor healthReducing premature mortalityImproving health inequalities. Method: One of the unique key factors for this project is the engagement of the communities; understanding problem areas and reviewing best practices. Methodologies from the early phase will be presented in this paper. Hot Spot Analysis. Pilot sites from across the region will be identified, within each of the pilot site a hot spot analysis will be undertaken to identify high rates of emergency hospital admissions. When matched against a combination of hospital and council data will identify socially and economically disadvantaged communities. Appreciative Inquiry is a recognised method for studying and changing social systems that builds on the core aspirations that exist within an individual or group seeking to introduce change. Using the method the project team together with local community champions will explore the health attitudes, beliefs and behaviours of residents and multiple agency professionals living and working within these communities, seeking together to identify and implement a range of interventions that will improve the health and wellbeing of residents. Conclusions: This paper introduces only the early phase of the project. Ultimately, it is crucial that the end result of the project reduces health inequalities and in doing so produces a model of health and social care delivery that will enable every child to have the best start in life.